Determinants of processed food exports from Vietnam to the European Union - Tuan, VU, Anh; Ninh, DOAN, Ngoc (International Journal of Innovative Research and Scientific Studies, 2025)
Vietnam possesses significant strengths in the export of agricultural products and food, and the EU is one of Vietnam’s largest import markets. This study examines the status quo and the factors affecting the export of processed food from Vietnam to the EU during the period of 2012-2023. The research combines qualitative and quantitative analyses. It investigates the key determinants influencing Vietnam’s processed food exports to the EU using a gravity model. Based on the evaluation of the current export situation and the analysis of influencing factors, the study proposes solutions to enhance the export of processed food from Vietnam to the EU in the coming years.